P124 Transcutaneous CO2 measurement in a long term ventilation (LTV) service. (11th November 2022) - Ong, WH; Lane, N; Messer, B; Tedd, H; Armstrong, A; Davidson, R; Ireland, P; Rodger, J; George, K; Cattermole, K; Madhu, Y; Fowkes, R; et al.
Abstract : Background: Transcutaneous CO2(TCCO2) measurement is widely used in the diagnosis and monitoring of ventilatory failure. Robust data on the success rates in measurement is scant. TCCO2 measurement requires a multimodal setup. We aimed to discern the factors affecting success rate of TCCO2 measurement in patients either referred or already under the care of a regional LTV service. We also aimed to determine if successful recordings influence management. Methods: All patients undergoing TCCO2 measurement between October 2019 and January 2022 were identified retrospectively. Notes were analysed for basic demographics, indications for TCCO2 measurement, measurement and device used (Radiometer TCM5 or Sentec), setup (ie.self, clinician or carer), inpatient or outpatient study, and how many attempts of TCCO2 measurement had occurred. Successful measurement was defined as adequate dataset for the clinical question not requiring repeat investigation. Statistical comparisons were made by Fisher's exact test. Results: We identified 435 recording events on 288 patients, mean age of 53, and 56% were males. 189(65.6%) had a neuromuscular disorder (NMD). The commonest indications for TCCO2 measurement were in those naïve to ventilation; 'assessment of diaphragmatic weakness or hypoventilation' (43.2%) and a second group established on treatment 'assessing adequacy of home ventilation therapy due to persistent symptoms' (27.2%). Overall TCM5 devices had statistically higher successful recording rates (197/268, 73.5%) than Sentec (100/165, 60.6%)[p=0.0056]. Similarly in outpatient studies, TCM5's success rate 187/253(73.9%) vs. Sentec's 94/154(61.0%) was significant [p=0.0079]. Inpatient studies trended correspondingly but failed to reach significance likely due to sample size. When comparing setup the same pattern was seen (Non-clinician setup: TCM 171/218(78.1%), Sentec 80/139(57.6%)[p<0.001] but note clinician setup was not significant (sample size, n=25). Upon successful TCCO2 measurement, 110/297(37%) progressed to new ventilation setup or a change in ventilator settings; notably in patients with diagnosis of NMDs [p=0.0001]. 9/44 of the recording events with successful measurement that were done routinely to monitor those already on ventilation resulted in ventilator settings change. Conclusion: Radiometer TCM5 had statistically significant higher success rates in our TCCO2 recordings. The reasons for this are unclear. Successful measurement can be helpful in decision making and there is a high success rate of domiciliary recordings.